2008
DOI: 10.1159/000147469
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits Predict Treatment Outcome in Alcohol-Dependent Patients

Abstract: Personality traits are important individual characteristics modifying responses to therapy in various diseases. The aim of this study was to identify personality traits that may predict treatment outcome in alcohol-dependent patients. The present analysis was based on a total of 146 alcohol-dependent patients (109 male, 37 female) after detoxification. The variable of interest was treatment outcome (abstinence/relapse) after a 1-year follow-up. To identify personality traits as predictors of treatment outcome,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 57 publications
5
68
1
2
Order By: Relevance
“…While most studies rely on subjective information based on interviews with patients and relatives or questionnaires asking when and how often patients started drinking alcohol again after abstinence [20,36,37], the present evaluation is based on a stricter but more objective criterion, i.e. the number of previous detoxifications asked in questionnaire 1, but confirmed by inspection of hospital records.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While most studies rely on subjective information based on interviews with patients and relatives or questionnaires asking when and how often patients started drinking alcohol again after abstinence [20,36,37], the present evaluation is based on a stricter but more objective criterion, i.e. the number of previous detoxifications asked in questionnaire 1, but confirmed by inspection of hospital records.…”
Section: Methodsmentioning
confidence: 99%
“…Since treatment outcome in alcohol dependence has also been found to be related to mood and anxiety disorders [5,6] as well as to the personality dimensions of psychoticism sensu Eysenck [18] (representing ruthlessness and antisocial behaviour) and lack of persistence [19,20], it was intended to investigate if the two types of personality traits, impulsivity and aggression on the one hand and the neuroticism-related traits of anxiety and depression on the other, are associated with liability to relapse after abstinence.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study found that among temperament dimensions persistence makes a significant contribution to the prediction of latency to relapse following inpatient alcohol-dependence treatment (37). Similarly, the risk of relapse was higher in alcohol dependent patients with a low score in persistence (38).…”
Section: Introductionmentioning
confidence: 91%
“…The literature on the link between impulsivity and addiction treatment outcomes clearly covers many other aspects than those discussed in the present paper, including personality aspects such as novelty and sensation seeking (Helstrom, Hutchison, & Bryan, 2007;Kahler et al, 2009;Patkar et al, 2004), attentional impulsivity (Charney, Zikos, & Gill, 2010) or lack of perseverance (Müller, Weijers, Böning, & Wiesbeck, 2008). These personality traits are typically assessed using self-report questionnaires, which may be less sensitive in identifying differences associated with treatment outcomes compared to neurocognitive tasks detailing specific behavioral processes.…”
Section: Limitations Of the Reviewmentioning
confidence: 99%